Implementation of KPKU (Kriteria Performa Kinerja Unggul) Method to Increase The Company Performance at PT. XYZ - Siswanto Siswanto; Singgih Saptadi; Arfan Bakhtiar (IPTEK Journal of Proceedings Series, 2020)
Gas and steam power plant (PLTGU) is a power plant that can operate very quickly from start-up to generate electric power as quick as fifteen minutes compared with steam power plant which takes eight hours. PLTGU can use gas fuel, HSD (High Speed Diesel), MFO (Marine Fuel Oil) as the operating fuel and so that can be said generating reliable and flexible because it can operate in two modes of cycle, open cycle and combine cycle. Power Plant performance sometimes does not match with what we expected, we need a strategy in order to achieve optimal performance. The problem is the generation performance decrease from its optimal condition due to the plant aging, operation and governance pattern. Power Plant XYZ has not achieved the expected performance from 2015 to 2018 which still below 95% averages out of expected target 95% to 100%. In order to improve the performance this research is used KPKU (Kriteria Performa Kinerja Unggul) methods which adopted from the Malcolm Baldrige Criteria for Performance Excellent (MBCFPE). The purpose of this study is to boost the company's competitive advantage, improve performance on an ongoing basis, and to achieve the vision and mission and objectives of the company.